'How` a multidisciplinary team worked effectively to reduce injury in a professional sport environment - Tee, J.; Rongen, F. (SportRxiv, 2020)
In professional team sport, managing injury risk depends on the effective collaboration of technical/tactical coaches, strength and conditioning coaches, sports medicine practitioners and sport scientists within a multidisciplinary team (MDT). Yet, to date no research has examined how these professionals might co-ordinate their efforts. The aim of this study is to examine the processes and interactions utilized by a demonstrably effective MDT. The efficacy of the MDT was established by quantifying the injury burden of the team across two seasons. The MDT achieved a 60% reduction in team injury burden during the second season (first season 516, 95%CI 491 to 542 vs. second season 205, 95%CI 191 to 219 days/1000 hours). Semi-structured interviews were conducted with all MDT members to determine each individual`s role within the injury prevention process and how these were co-ordinated between disciplines. Thematic analysis identified three key constructs that contributed to the MDT`s success; 1) shared values, 2) expertise and 3) the effective operationalization of underpinning values and expertise. Shared values expressed by the MDT members included `future performance is driven by healthy performers`, and shared responsibility for injury prevention. All MDT members were experts in their own fields but identified that they had to learn how to be effective within the environment and required skill in building interpersonal relationships. The operationalisation of these principles took place through iterative plan-do-review cycles underpinned by sophisticated data collection and monitoring and the provision of time and resource to complete these operations. This research offers insights into "how" effective MDTs work to achieve injury reduction, and the models and processes presented will inform practice for other MDTs working in sport.